NATURE AND THE SPECIFIC FEATURES OF THE DEVELOPMENT OF POLYPHONIC HEARING - Zavadska, Galina; Bagele, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Polyphonic hearing is a component of musical hearing. Polyphonic hearing implies the ability to perceive a simultaneous motion of two or more separate voices within the general sound fabric of a musical piece. Polyphonic hearing can be developed like all other sides of musical hearing. The development of polyphonic hearing can be enhanced by different work forms at the lessons in sol-fa: intoning, analysis by ear, many-voiced music dictation. The development of different sides of musical hearing during the process of work on solfeggio is really essential for a future musician-professional. Research aim: to determine the specific features of polyphonic hearing and characterize its developmental stages.On the basis of long pedagogical experience, this paper reveals the specificity of polyphonic hearing, identifies and characterizes its developmental stages in the process of work on sol-fa.